The Influence Of Motivation And Competency On Competitive Advantage In The Project Solution Portofolio At Telkom Property Regional 6 Kalimantan - Sulthoni, Nurrokhmat; Djunita Pasaribu, Rina (International Journal of Science, Technology & Management, 2025)
The Project Solution portfolio remains a key driver in increasing revenue and profitability within the company. As evidenced by the four existing portfolios, Project Solution contributes an average of over 30% of annual revenue, particularly in Region 6 Kalimantan. Furthermore, the ongoing and upcoming IKN (National Capital City) project presents a significant opportunity to increase revenue within this portfolio. With the company's competitive advantages, revenue contributions should be maximized or even increase compared to previous years. Are there any obstacles or problems encountered by personnel involved in this project that have resulted in suboptimal contributions, or even decreased, compared to previous years? This is one of the reasons we focus on researching project-related human resources.The aim of the research is to determine the motivation of each individual involved in a project, to determine the competency of each individual involved in a project and to determine the influence of motivation and competency on competitive advantage in the Project Solution portfolio. The approach used in this research is quantitative. A quantitative approach is used to research a specific population or sample, collecting data using research instruments, and analyzing the data using quantitative/statistical methods. The research results show that motivation does not significantly influence competitive advantage, competence significantly influences competitive advantage, while simultaneously motivation and competence can explain the competitive advantage construct by 67.2% using a moderate model. The remaining variability not explained by the construct could be caused by other factors outside the model. From the results of this study, competence has a significant influence on competitive advantage rather than employee motivation, so the initial focus is to maintain employee competence so that it remains in the very competent category or even improved and retain employees who have good competence to continue working in the company.